Assessing sovereign risk: the case of rich countries. Issue 3 (29th July 2014) - Gaillard, Norbert
Abstract : Purpose: – This paper aims to shed new light on the inability of credit rating agencies (CRAs) to forecast the recent defaults and so-called quasi-defaults of rich countries. It also describes how Moody's sovereign rating methodology has been modified – and could be further improved – to solve this problem. Design/methodology/approach: – After converting bond yields into yield-implied ratings, accuracy ratios are computed to compare the respective performances of CRAs and market participants. Then Iceland's and Greece's ratings at the beginning of the Great Recession are estimated while accounting for the parameters included in the new methodology implemented by Moody's in 2013. Findings: – Market participants outperformed Moody's and Standard & Poor's in terms of anticipating the sovereign debt crisis that hit several European countries starting in 2008. However, the new methodology implemented by Moody's should lead to more conservative and accurate sovereign ratings. Originality/value: – The chronic inability of CRAs to anticipate public debt crises in rich countries is dangerous because the countries affected – which are generally rated in the investment-grade category – are substantially downgraded, amplifying the sovereign debt crisis. This study is the first to demonstrate that Moody's has learned from its recent failures. In addition, it recommends ways to detect serious threats to the creditworthiness of high-income countries.